"By the Author of The Leavenworth Case" or Capitalizing on Reader Appetite for the Bestselling Novelist: Female Detection, Transatlantic Popular Fiction and Anna Katharine Green's The Mill Mystery (1886). Issue 2 (2nd April 2016) - Rooney, Paul
ABSTRACT: Anna Katharine Green's The Leavenworth Case (1878) was a bestselling detective novel that found favour on both sides of the Atlantic. Taking this critically neglected American writer as an example, this article considers the creative strategies open to the popular novelist looking to capitalize on her debut work's realization of such a level of commercial success that the title came to constitute a brand in the literary marketplace. The inadequacies in transatlantic copyright during the 1880s left Green susceptible to unauthorized reprinting of her work by English publishers seeking to take advantage of her cachet. This led her to enter into compromise arrangements with said houses, which both elevated and diminished her stock. Probing the roots of Green's appeal in England, this article demonstrates how her work formed part of a pre-Sherlock Holmes wave of detective fiction. While Green was adept at writing absorbing fiction that found favour with diverse reading constituencies, she also sought to use the detective novel as a vehicle for social comment on issues of gender. In her 1886 novel The Mill Mystery, which featured her first fictional female detective, Green sought to reconcile a meditation on female agency with the constraints of working within a genre fiction context and under the shadow of her bestselling debut.